Unified process for adaptive Semantic Web service composition - Slabospitskaya, О.A. (PROBLEMS IN PROGRAMMING, 2018)
New technological for the Process of Semantic Web service on-line composition, that is adaptive (able to change its behavior to meet new requirements and to fit new (un)foreseen situations) and usable by third parties, to maintain (non)anticipatory changeable business processes model is elaborated. Consistently with the adaptive service’s previous model as Dynamic Line of Semantic Services for providing business processes’ actors with anticipated Functions over the stages between the alterations of these actors’ needs, the Process being modeled is considered as the sequence of stages for the above Line’s Services composing that are unified as for composition method (at the functional and process level). The stage is composed with the Line’s Variability Management functions’ operations (forming/adapting Functions Model and Service Platform, composing Services for these Functions, Variability services for this functions, diagnostic monitoring) in the common information environment governed with the Functions Model. Implementing of the described Process within business processes with unstable and heterogeneous contexts will enhance their usage and re-engineering.Problems in programming 2018; 1: 65-76